Numerical Investigation of Light Emission from Quantum Dots Embedded into On‐Chip, Low‐Index‐Contrast Optical Waveguides. Issue 7 (15th February 2019) - Hoehne, Theresa; Schnauber, Peter; Rodt, Sven; Reitzenstein, Stephan; Burger, Sven
Abstract : Single‐photon emitters integrated into quantum optical circuits will enable new, miniaturized quantum optical devices. Here, we numerically investigate semiconductor quantum dots embedded into low‐refractive‐index‐contrast waveguides. We discuss a model to compute the coupling efficiency of the emitted light field to the fundamental propagation mode of the waveguide, and we optimize the waveguide dimensional parameters for maximum coupling efficiency. Further, we show that for a laterally cropped waveguide the interplay of Purcell enhancement and optimized field profile can enhance the coupling efficiency by a factor of about two. Abstract : Tailoring the lateral structure of ridge waveguides can enhance the coupling of light emitted by embedded quantum dots into the fundamental transverse electric mode and increases the overall single‐photon device efficiency. The authors present a study on the coupling efficiency and on the Purcell factor of a GaAs/AlGaAs waveguide under different geometrical aspects and propose a method to improve and direct the coupling.